An attempt toward the generalized Langevin dynamics simulation - Kim, B.; Chong, S.-H.; Ishizuka, R.; Hirata, F. (Condensed Matter Physics, 2008)
An attempt to generalize the Langevin dynamics simulation method is presented based on the generalized Langevin theory of liquids, in which the dynamics of both solute and solvent is treated by the generalized Langevin equations, but the integration of the equation of motion of solute is made in the manner similar to the ordinary molecular dynamics simulation with discretized time steps along a trajectory. A preliminary result is derived based on an assumption of the uniform solvent density. The result is regarded to be a microscopic generalization of the phenomenological Langevin theory for the harmonic oscillator immersed in a continuum solvent developed by Wang and Uhlenbeck. Представлено спробу узагальнити метод моделювання ланжевенiвської динамiки на основi узагальненої ланжевенiвської теорiї рiдин, в яких динамiка i домiшки i розчинника розглядається узагальненими рiвняннями Ланжевена, але iнтегрування рiвнянь руху домiшки робиться подiбним чином до звичайного методу молекулярної динамiки з дискретизованим часовим кроком вздовж траєкторiї. Отримано попереднiй результат, що грунтується на припущеннi однорiдної густини розчинника. Результат трактується як мiкроскопiчне узагальнення феноменологiчної ланжевенiвської теорiї для гармонiчного осцилятора, помiщеного у суцiльне середовище розчинника, що розроблялась Ванґом та Уленбеком.